Sufis, Sufi ṯuruq̲ and the question of conversion to Islam in India : an assessment - Massoud, Sami (McGill University, 1997)
The purpose of this thesis is to analyze the topoi found in various writings on the Indian subcontinent, which depict Muslim mystics, the Sufis, as responsible for the conversion, forced or peaceful, of non-Muslim Indians to Islam. Our analysis of various historiographical traditions produced in the Subcontinent between the eleventh and the twentieth centuries, will show that this image of Sufis qua missionaries is more the result of socio-political considerations (legitimization of imperial order; posthumous images of Sufis in the eyes of different folk audiences, etc.) than the reflection of historical reality. This thesis also examines the processes, most of them indirect, in which Sufis were involved and which on the long run led to the acculturation and to the Islamization of certain non-Muslim groups, thus opening the way for the birth and then consolidation of a Muslim identity.
Keywords: Muslim converts -- India.; Sufis -- India.; Sufism -- India.